Peran Kinerja Produk terhadap Kepuasan Pelanggan PT. Aceplas Indonesia - Muhammad Octavian; Budi Astuti (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to determine the role of product performance which is measured based on product quality perceptions on customer satisfaction at PT. Aceplas Indonesia, and the role of product performance which is measured based on service quality on PT customer satisfaction. Aceplas Indonesia. This research approach uses a qualitative approach. The subjects of this research were 1 head of marketing, 1 head of planning, 1 head of production and 2 consumers. In this research, the methods used in collecting data were interviews and documentation. The data analysis technique uses the analysis model from Miles & Huberman. This analysis includes data collection, data reduction, data presentation, and conclusions. The data validity technique uses source triangulation techniques. The research results show that perception of product quality of PT. Aceplas Indonesia has an impact on customer satisfaction, and PT service quality. Aceplas Indonesia has an impact on customer satisfaction.